Applying of Five Family Duties at Patient Family Diabetes Millitus in Pliken Kembaran II Banyumas - Ani Kuswati; Wahyudi Wahyudi; Ratifah Ratifah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
This study aimed to analyze application of five family duties in health area in taking care of member of family suffering Diabetus Mellitus. This was a qualitative research with fenomenologis approach, with data collecting method indepth interview. Participant of this study were selected to have certain criterion that is one of member family is suffering Diabetes mellitus. Result of this research indicated that family to recognize Diabetes mellitus after contact with health facility. Decision taken by family is strive health or brings to health service, the treatment is give nutrition and takes medicine regularly. Workdload of family and knowledge in accomplishment of economic requirement influences psychological of patient especially in arrangement of area which kondusif.